Current Controversies in the Prediction, Diagnosis, and Management of Cerebral Vasospasm: Where Do We Stand? - Young Lee; Scott L. Zuckerman; J. Mocco (Neurology Research International)
Aneurysmal subarachnoid hemorrhage occurs in approximately 30,000 persons in the United States each year. Around 30 percent of patients with aneurysmal subarachnoid hemorrhage suffer from cerebral ischemia and infarction due to cerebral vasospasm, a leading cause of treatable death and disability following aneurysmal subarachnoid hemorrhage. Methods used to predict, diagnose, and manage vasospasm are the topic of recent active research. This paper utilizes a comprehensive review of the recent literature to address controversies surrounding these topics. Evidence regarding the effect of age, smoking, and cocaine use on the incidence and outcome of vasospasm is reviewed. The abilities of different computed tomography grading schemes to predict vasospasm in the aftermath of subarachnoid hemorrhage are presented. Additionally, the utility of different diagnostic methods for the detection and visualization of vasospasm, including transcranial Doppler ultrasonography, CT angiography, digital subtraction angiography, and CT perfusion imaging is discussed. Finally, the recent literature regarding interventions for the prophylaxis and treatment of vasospasm, including hyperdynamic therapy, albumin, calcium channel agonists, statins, magnesium sulfate, and endothelin antagonists is summarized. Recent studies regarding each topic were reviewed for consensus recommendations from the literature, which were then presented.